Academic Senate Minutes 2009-10-29 - Academic Senate:::::::::
Chair Report. Agenda approved. Minutes of 10/1/09 amended and approved. President's Report. Provost's Report. Vice President of SAEM's Report. Associated Students' Report. CFA Report. EPC Report. Chair-Elect's Report. By-Laws Revision: Charge of SAC referred back to SAC. Resolution on a Diversity Coordinator for Academic Affairs approved. Good of the Order.